2017
DOI: 10.1186/s12864-016-3427-2
|View full text |Cite
|
Sign up to set email alerts
|

Age influences the olfactory profiles of the migratory oriental armyworm mythimna separate at the molecular level

Abstract: BackgroundThe oriental armyworm Mythimna separata (Walk) is a serious migratory pest; however, studies on its olfactory response and its underlying molecular mechanism are limited. To gain insights to the olfactory mechanism of migration, olfactory genes were identified using antennal transcriptome analysis. The olfactory response and the expression of olfactory genes for 1-day and 5-day-old moths were respectively investigated by EAG and RT-qPCR analyses.ResultsPutative 126 olfactory genes were identified in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 82 publications
3
23
1
Order By: Relevance
“…There are three previous studies antennal on transcriptome of M. separata. He et al (2017) identified 126 olfactory genes including 43 ORs, 13 GRs, 16 IR, 37 OBPs, 14 CSPs, and 3 SNMPs [ 58 ], Chang et al (2017) obtained 130 chemosensory genes encoding 71 ORs, 1 GR, 8 IRs, 32 OBPs, 16 CSPs, and 2 SNMPs [ 59 ] and Liu et al (2017) gained 60 ORs, 8 GRs, 24 IRs, 50 OBPs, 22 CSPs and 2 SNMPs [ 60 ]. Compared with Liu’s study which was also on the head transcriptome of M. separate , we identified some novel chemosensory genes and the lengths of the genes were significantly longer.…”
Section: Discussionmentioning
confidence: 99%
“…There are three previous studies antennal on transcriptome of M. separata. He et al (2017) identified 126 olfactory genes including 43 ORs, 13 GRs, 16 IR, 37 OBPs, 14 CSPs, and 3 SNMPs [ 58 ], Chang et al (2017) obtained 130 chemosensory genes encoding 71 ORs, 1 GR, 8 IRs, 32 OBPs, 16 CSPs, and 2 SNMPs [ 59 ] and Liu et al (2017) gained 60 ORs, 8 GRs, 24 IRs, 50 OBPs, 22 CSPs and 2 SNMPs [ 60 ]. Compared with Liu’s study which was also on the head transcriptome of M. separate , we identified some novel chemosensory genes and the lengths of the genes were significantly longer.…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic analysis of CSPs from different insect species shows that CSPs are highly conserved and possess a characteristic N-terminal signature motif ( Wanner et al, 2004 ; ForĂȘt et al, 2007 ). CSPs perceive and bind external ligands, which result in action potentials that contribute to subsequent behaviors ( Tunstall and Warr, 2012 ; He Y. et al, 2017 ). Previous studies have shown that CSPs are exclusively expressed in the antennae of Sesamia inferens ( Zhang et al, 2014 ), Polistes dominulus ( Calvello et al, 2003 ), Linepithema humile ( Ishida et al, 2002 ), Cerapachys biroi ( Mckenzie et al, 2014 ) and other insect species.…”
Section: Introductionmentioning
confidence: 99%
“…Like other moth species, My. separata relies on olfaction for locating food and mates ( He et al, 2017 ). In addition, My.…”
Section: Introductionmentioning
confidence: 99%